2015
DOI: 10.1109/tmag.2015.2404303
|View full text |Cite
|
Sign up to set email alerts
|

A Partially Magnetized Ferrite LTCC-Based SIW Phase Shifter for Phased Array Applications

Abstract: The theory and design of a half mode SIW ferrite LTCC based phase shifter is presented in this work. Unlike typical ferrite based designs, the biasing is done through embedded windings in a multilayer substrate which not only obviates the requirement of bulky electromagnets but also prevents loss of bias fields at the air-to-ferrite interface. The phase shifter is operated in the partially magnetized state of ferrite substrate. Through the combined effect of embedded windings, half mode waveguide operation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…As integral microwave components, phase shifters have been demonstrated miniaturization using LTCC ferrite tapes [1][2][3][4][5]. One member of gyromagnetic materials, LiZnTi ferrites have been investigated and applied in phase shifters due to their high Curie temperature, excellent temperature stability, high remanence square ratio, wide range of saturation magnetization, and low cost [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As integral microwave components, phase shifters have been demonstrated miniaturization using LTCC ferrite tapes [1][2][3][4][5]. One member of gyromagnetic materials, LiZnTi ferrites have been investigated and applied in phase shifters due to their high Curie temperature, excellent temperature stability, high remanence square ratio, wide range of saturation magnetization, and low cost [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This value is low as compared to the simulated value of 3.0 dBi. As discussed before, this low gain performance from the antenna is due to the high surface roughness value (4.5 m) measured for the substrate and the conductor [14], [15]. In order to verify this effect, the measured surface roughness value is used in the simulator for the post-measurement simulations.…”
Section: B Gain and Radiation Pattern Measurementsmentioning
confidence: 99%
“…However, these antennas are designed to operate in the saturated state of the ferrite substrates. The authors have previously reported several tunable and reconfigurable microwave passive components on the partially magnetized ferrite Low Temperature Co-fired Ceramic (LTCC) substrate [13]- [15]. Although, the theory and measurements of these microwave components show the viability of operating the ferrite substrates in the unsaturated state, the cost of the ferrite LTCC technology is significant.…”
Section: Introductionmentioning
confidence: 99%
“…1(b). Previously, half mode ferrite based substrate integrated waveguide (SIW) has been used for phase shifter design [6]. In that work it is shown that a half mode waveguide can improve the efficiency by reducing the number of magnetostatic bias sources.…”
Section: Introductionmentioning
confidence: 99%